The Role of 18F-FDG-PET and PET/CT in Patients with Colorectal Liver Metastases Undergoing Selective Internal Radiation Therapy with Yttrium-90: A First Evidence-Based Review - Salvatore Annunziata; Giorgio Treglia; Carmelo Caldarella; Federica Galiandro (The Scientific World Journal)
Purpose. To provide a first evidence-based review of the literature on the role of fluorine-18-fluorodeoxyglucose positron emission tomography and positron emission tomography/computed tomography (FDG-PET and PET/CT) in patients with colorectal liver metastases (CRLM) undergoing selective internal radiation therapy (SIRT) with yttrium-90 (90Y) microspheres. Methods. A comprehensive computer literature search was conducted to find relevant published articles on whole-body FDG-PET or PET/CT in patients with CRLM undergoing SIRT. Results. We identified 19 studies including 833 patients with CRLM undergoing SIRT. The role of FDG-PET or PET/CT was analysed in treatment planning, treatment response evaluation, and as prognostic tool. Conclusion. FDG-PET and PET/CT provide additional information in treatment evaluation of CRLM patients treated with SIRT and may have a role in treatment planning and patient selection. FDG-PET/CT is emerging as good prognostic tool in these patients.